A life-threatening complication in a child with cerebral palsy: Tracheoinnominate artery fistula case report - Ayla Ece Celikten; Gorkem Yigit; Kudret Atakan Tekin; Ufuk Turkmen (Turkish Journal of Vascular Surgery)
Tracheoinnominate artery fistula represents a severe complication of tracheostomy. Key factors that determine patient outcomes include rapid diagnosis, immediate bleeding control while maintaining airway patency, and urgent surgical intervention, whether or not the innominate artery is interrupted. This case report discusses the clinical management of a 13-year-old male patient with cerebral palsy and a long-term tracheostomy who presented with massive tracheal bleeding. [Turk J Vasc Surg 2025; 34(1.000): 83-6]